HUBUNGAN FAMILY INVOLVEMENT DAN INTERAKSI PEER GROUP DENGAN SELF-EFFICACY MENJAUHI SEKS BEBAS PADA REMAJA DI SMAN 85 JAKARTA - Putri Zalfa, (2020)
Teenage sexual maturity encourages adolescents to engage in sexual behavior. Sexual behavior in adolescents occurs everywhere, especially in Jakarta. Self-efficacy influences adolescents in avoiding free sex and rejecting unwanted sex. Family as a source of self-efficacy that is involved with adolescents is able to play a role in delaying sexual debut and preventing free sex, while peers also influence sexual behavior through interactions within peer groups. This study aims to determine the relationship of family involvement and peer group interaction with self-efficacy avoding free sex in adolescents at SMAN 85 Jakarta. This type of research is quantitative with a cross sectional analytic descriptive approach. A sample of 223 adolescents using simple random sampling technique. Chi-Square analysis results show that there is a significant relationship between family involvement with self-efficacy avoiding free sex with Pvalue: 0.000 and there is a significant relationship between peer group interaction with self-efficacy avoiding free sex in adolescents with Pvalue: 0,000. Suggestion for adolescents is to increase self-efficacy and to be closer to family and to choose positive peer group interactions to be able to avoid free sex.